WOMEN AUDIENCE INTERPRETATION TOWARDS BEAUTY CONSTRUCTION IN INSTGARAM ACCOUNT OF UNDIP CANTIK - Septiyani, Indriastuti; ., Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
This research was conducted to find out how the meaning done by women audiences towards beauty construction that exist in Instagram account of Undip Cantik. Instagram is a photo-based social media and is part of a new media that is able to provide information to its users, Instagram users can also share information including also spread the ideology. The beauty constructions displayed by the media have been a myth which still trapping women, as this is the standard of quality for women, making women lose their identity and make women being objectified. Though beauty is a construction of patriarchal and this shows that women are dominated by male domination. This research uses a critical paradigm and uses analysis method the analysis of receptions by Stuart Hall to determine the meaning of audiences. This research uses Roland Barthes semiotics analysis to find out the dominant meanings that appear in the text photo of Undip Cantik.. The main theory in this reasearch is the counter hegemony of Antonio Gramsci. This theory is to reveal that the audience of media do not accept all the ideology on the media because audiences are active producing meaning thus they have alternatives idea from the media hegemony. This research also use beauty myth theory by Naomi Wolf to see the beauty discourse in Undip Cantik. Preferred reading from the text of Undip Cantik is the construction built by patriarchal culture to make women as object to get pleasure. The result of this research shows that there is meaning diversity toward beauty discourse on Undip Cantik photo text. This result shows that the some informants knows the dominant meaning of the photo text but they still negotiate and they even ignore the dominant messages in certain cases to be applied on them or other women. The informants of this research also considered as active audience because they are able to interpret the messages but they do not easily accept all the messages they recieved from media.